ChemInform Abstract: Synthesis, Characterization, and Computation of Catalysts at the Center for Atomic‐Level Catalyst Design. Issue 42 (14th October 2014) - Spivey, James J.; Krishna, Katla Sai; Kumar, Challa S. S. R.; Dooley, Kerry M.; Flake, John C.; Haber, Louis H.; Xu, Ye; Janik, Michael J.; Sinnott, Susan B.; Cheng, Yu‐Ting; et al., et al.
Abstract Review: 229 refs.